EVALUASI INOVATIF KEBIJAKAN PERENCANAAN PENDIDIKAN ISLAM: STRATEGI OPTIMALISASI UNTUK MENINGKATKAN RELEVANSI PENDIDIKAN BERBASIS NILAI BUDAYA DAN MODERNITAS - Anissa, Desi Dwi; Syafi’i, Asrop; Anam, Khoirul (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2024)
This research examines the innovative evaluation of Islamic education planning policies at the Al Kamal Integrated Islamic Boarding School, which focuses on the challenges of integrating Islamic values ​​with the demands of modernity. The main problem is how to manage education policies that are relevant to current developments without losing Islamic identity. The aim of this research is to assess the effectiveness of Islamic education policies, especially in cognitive, affective, psychomotor and spiritual aspects, as well as how this integration is implemented in Islamic boarding schools. The research uses a case study method with a descriptive qualitative approach. Data was collected through observation, in-depth interviews and documentation studies. Analysis was carried out by triangulating data from various sources to obtain valid results. Correlation and survey evaluation models are used to understand the impact of policies on student learning outcomes and the relevance of education to current social needs. The research results show that policy evaluation is carried out through various stages, from daily to annual evaluations, to ensure the achievement of educational goals both in terms of academics and character formation. Policies that combine traditional education and modernity, such as strengthening technological skills and foreign languages, have proven capable of preparing students to face global challenges without losing their Islamic identity. The involvement of caregivers, teachers, parents and alumni also plays an important role in the successful implementation of this policy.